2018
DOI: 10.1007/s11248-018-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Zygote injection of RNA encoding Cre recombinase results in efficient removal of LoxP flanked neomycin cassettes in pigs

Abstract: Genetically engineered pigs are often created with a targeting vector that contains a loxP flanked selectable marker like neomycin. The Cre-loxP recombinase system can be used to remove the selectable marker gene from the resulting offspring or cell line. Here is described a new method to remove a loxP flanked neomycin cassette by direct zygote injection of an mRNA encoding Cre recombinase. The optimal concentration of mRNA was determined to be 10 ng/μL when compared to 2 and 100 ng/μL (P < 0.0001). Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…S1e, f). When reconstructed embryos were cultured for 6 days, almost no difference of blastocyst rates between Dox-treated (19.5%, 40/205) and Dox-untreated (20.4%, 23/113) groups was observed, while the previous report showed that zygote injection of RNA encoding Cre recombinase resulted in reduction of blastocyst rate [ 26 ], indicating that Dox-dependent SpCas9 expression may have less negative impact on porcine embryo development than Cre recombinase expression. These results suggested that the established DIC system in pigs could result in Dox-dependent SpCas9 expression at the cellular and embryonic level.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…S1e, f). When reconstructed embryos were cultured for 6 days, almost no difference of blastocyst rates between Dox-treated (19.5%, 40/205) and Dox-untreated (20.4%, 23/113) groups was observed, while the previous report showed that zygote injection of RNA encoding Cre recombinase resulted in reduction of blastocyst rate [ 26 ], indicating that Dox-dependent SpCas9 expression may have less negative impact on porcine embryo development than Cre recombinase expression. These results suggested that the established DIC system in pigs could result in Dox-dependent SpCas9 expression at the cellular and embryonic level.…”
Section: Resultsmentioning
confidence: 87%
“…Additionally, genomic damages [ 20 , 21 ], off-target effects [ 22 , 23 ], and immunological clearance responses [ 24 ] caused by uncontrollable Cas9 expression, will hinder the application of animal models with this constitutively Cas9-expressing system, which is also not avoidable for inducible expression systems based on the Cre-recombinase system, in which sustainable constitutive Cas9 expression exist after activation [ 16 , 25 ]. Furthermore, Cre-recombinase was confirmed to negatively affect porcine embryonic development [ 26 ] and to be potentially genotoxic with pseudo recombination sites in mammalian genomes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cre recombinase expression in the germ line of mice would result in abnormal arrangement of chromosomes and infertility, which might be due to the unexpected interactions of pre‐existing pseudo loxP sequences in the presence of Cre in vivo [85]. Microinjection of Cre mRNA into pig embryos at a high dose could lead to embryonic toxicity, which may indicate the presence of pre‐existing pseudo loxP sequences in the swine genome [86].…”
Section: Swine Models With Recombinase‐specific Recognition Elementsmentioning
confidence: 99%
“…By 2018, Whitworth et al had developed a method that utilized the CRISPR/Cas9 technology to remove a loxP flanked neomycin cassette by direct zygote injection of RNA encoding Cre recombinase. This new technique can be used to efficiently remove selectable markers in genetically engineered animals without the need for long-term cell culture and subsequent somatic cell nuclear transfer (SCNT) [67]. Almost certainly, it has a very promising future for transgenic pigs with the advantages of enhancing body growth and minimizing environmental pollution that would be created by the CRISRP/Cas9 method.…”
Section: Applications In Transgenesis and Beyondmentioning
confidence: 99%